Comparison of Methods for Evaluating Stability Performance of Power System Stabilizers - Hiramsson, Joakim (My University, 2017)
Two methods are commonly used by transmission system operators to evaluate the stability performance of a power system stabilizer (PSS). However, cases have been encountered where the two evaluation methods do not agree. This is problematic since it may affect the stability of the power system. In this study it is investigated and suggested which of two evaluation methods that is better to use when evaluating the stability performance of a PSS. This study is based on dynamic simulations of the Nordic32-system where PSS2Bs are placed at different synchronous machines that are located at different buses in the power system; then, the impact of tuning the PSS2Bs according to the two evaluation methods is analyzed by the traditional method of eigenvalue analysis. The eigenvalue analysis shows that tuning of the PSS2Bs according to the evaluation method used by Statnett results in higher increases in the damping ratios of the complex eigenvalues with imaginary parts in the range of 0.6 - 6.3 rad/s compared with tuning of the PSS2Bs according to the evaluation method used by National Grid. Therefore, for the specific cases simulated, it is suggested that the evaluation method used by Statnett is better to use for purposes of evaluating the stability performance of a PSS.
Keywords: Elkraftteknik; Electric power engineering